PENERAPAN REGULAR EXPRESSION DALAM MELINDUNGI ALAMAT EMAIL DARI SPAM ROBOT PADA KONTEN WORDPRESS - Agus Muliantara (Jurnal Ilmu Komputer, 2009)
Email as a progress of information technology and telecommunications has connected millions of people around the world. However, over the development, there are developments that may harm called a spam robot. Where is the spam robots will explore every email address in the entire website and then sending alot of ads to those email address. There are several ways to protect email addresses on a site that is to change the text-based email address into image. So to prevent spam robots parsing of email addresses.This research carried out by taking a case study on the site using the Content Management System (CMS) Wordpress, with aims to make development on the wordpress site content so that each email address that is written by default will automatically be converted into images.From the testing carried out the results that the development can run better. The application able to change the email address written in the standard form into image automatically